PERBEDAAN HARGA SAHAM DAN AKTIFITAS VOLUME PERDAGANGAN SAHAM LQ-45 SEBELUM DAN SESUDAH TEROR BOM THAMRIN - Doni Saputra; Dewi Rahmayanti (Universitas Teuku Umar, 2016)
This study examined the difference in stock price and trading volume activity pra-event day and post event day Thamrin terror bombings that occurred on January 14, 2016. Samples taken in this study were 45 companies incorporated in the LQ-45 in the Indonesian Stock Exchange. Analysis techniques data used in statistical tests in this study using Paired Sample t-Test and the Wilcoxon signed rank test. Overall the research stock prices at the beginning of the terror bombings occurred Thamrin there are significant differences in the share price LQ-45 pra and post the terror bombing Thamrin. The stock price difference is significant shares occurred on 1 day, 2 days, 4 days, and 6 days pra and post the terror bombing Thamrin. In trading volume activity there are significant differences in the activity of stock trading volume 1 day and 10 days pra and post the terror bombing Thamrin. Overall there are no significant differences in the trading volume activity in the shares of LQ-45 pra and post the terror bombing Thamrin.